2014
DOI: 10.1088/2053-1591/1/3/036501
|View full text |Cite
|
Sign up to set email alerts
|

Surface oxidation and phase transformation of the stainless steel by hybrid laser-waterjet impact

Abstract: Hybrid jets (laser guided by water jet) are commonly used in the area of microelectronics for cutting thin wafer plates and for the design of special pieces. In this context, the hybrid jet works with a low power and low pressure. Efforts are made to apply and to improve this hybrid technology for cutting thicker metallic materials. In order to facilitate this development, we have studied the effects induced by a water jet-laser system coupled to the same point on a metallic material. The pressure of the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The different oxides found in this study are the same than which were found in other type of high-energy cutting process like laser-water jet cutting [24] but their presence has not been explained accurately through temperatures analysis. The temperatures given in Fig.…”
Section: Oxides Detection By Raman Spectroscopy Up and Resultssupporting
confidence: 38%
“…The different oxides found in this study are the same than which were found in other type of high-energy cutting process like laser-water jet cutting [24] but their presence has not been explained accurately through temperatures analysis. The temperatures given in Fig.…”
Section: Oxides Detection By Raman Spectroscopy Up and Resultssupporting
confidence: 38%
“…Excepted for the cutting speed now varying from 5 to 20 mm/min rated in steps of 1 m/min, the experimental parameters, instruments and machines are the same as those of our previous works, here being summarized, i.e. a Yb:YAG laser (wavelength = 1030 nm, spot size = 113µm, power = 400 W) ; water pumped at 1 MPa through a 0.25mm nozzle diameter [11]. The optimal cutting speed with small-oxidized zone and net shape quality cut is found to be equal to 11 m/min.…”
Section: Methodsmentioning
confidence: 99%
“…Due to this high applicative potential, in a previous paper, we have presented experimental results and interpretations of the structural changes and phase transformations during cutting of stainless steel with a coupled Laser Water Jet (LWJ) converging on the surface [11]. Using a 400 W laser, we have shown by different characterization techniques that due to the deposited energy, the reactivity of water molecules with the surface greatly increases, creating an exotic oxidation of the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, the Gaussian beam is focused to the center of the nozzle through a focusing mirror, and is fully reflected to the surface of the workpiece in a laminar water column to remove the workpiece. Water-jet guided laser technology has been widely used in the processing of difficult-to-machine materials such as composite materials and superalloys due to its high machining accuracy and small heat-affected zone [3][4][5] . When water-jet guided laser technology is used to process materials, its high-pressure water column can quickly remove the resulting melt, making the cutting efficiency high and the heat affected zone small.…”
Section: Introductionmentioning
confidence: 99%